Virtual Manipulatives with Integrated Sign Language: Digital Innovation in Mathematics Learning for Deaf-Mute Students in Inclusive Elementary School - Antara, I Gede Wahyu Suwela; Suarjana, I Made; Simamora, Alexander Hamonangan; Deng, Jian Bang (DIKODA JURNAL PENDIDIKAN SEKOLAH DASAR, 2025)
This study aims to examine the validity of sign language-based virtual manipulatives media for teaching mathematics to deaf-mute students in inclusive elementary schools. The research employed a Research and Development (R&D) method using the ADDIE development model. Validation was conducted by three categories of experts: media expert, inclusive instructional design expert, and mathematics content expert. The instrument used was a validation sheet featuring a Likert scale and a qualitative feedback column. The validation results showed that the media achieved an average score of 94.73%, placing it in the "very valid" category. These findings indicate that the developed media has met technical, pedagogical, and inclusive criteria and is feasible for use in the implementation stage of learning. This research contributes to the development of adaptive and accessible digital learning media for students with special needs, particularly those who are deaf-mute, and supports the implementation of quality inclusive education.